1994
DOI: 10.1016/0014-5793(94)00570-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuromedin B receptor, expressed in Xenopus laevis oocytes, selectively couples to Gαq and not Gα11

Abstract: G-proteins of the q family have been implicated as mediators of bombesin receptors action. We cloned Xenopus G, and G,,, and specifically disrupted the synthesis of either protein with selective antisense oligonucleotides. CC14 antisense inhibited responses mediated by neuromedin B receptor (NMB-R) by 74%, though not by gastrin-releasing peptide receptor (GRP-R). G,,, antisense had little effect on either GRP-R-or NMB-R-mediated responses. This suggests that NMB-R couples to G,_, and that GRP-R and NMB-R show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…Similar pertussis toxin-insensitive activations of phospholipase C leading to intracellular Ca 2ϩ signals have been shown previously for the expression of other G-protein-coupled receptors in Xenopus oocytes, including the M 3 -muscarinic receptor (Stehno-Bittel et al, 1995), the thyrotropin-releasing hormone receptor (Quick et al, 1994;de la Penna et al, 1995), and the neuromedin B receptor (Shapira et al, 1994). This again contrasts with studies on the expression of vertebrate D1-like receptors in rat pituitary GH 4 C 1 cells and SK-N-MC neuroblastoma cells in which no evidence of coupling to G q␣ could be found (Kimura et al, 1995).…”
Section: Discussionsupporting
confidence: 72%
“…Similar pertussis toxin-insensitive activations of phospholipase C leading to intracellular Ca 2ϩ signals have been shown previously for the expression of other G-protein-coupled receptors in Xenopus oocytes, including the M 3 -muscarinic receptor (Stehno-Bittel et al, 1995), the thyrotropin-releasing hormone receptor (Quick et al, 1994;de la Penna et al, 1995), and the neuromedin B receptor (Shapira et al, 1994). This again contrasts with studies on the expression of vertebrate D1-like receptors in rat pituitary GH 4 C 1 cells and SK-N-MC neuroblastoma cells in which no evidence of coupling to G q␣ could be found (Kimura et al, 1995).…”
Section: Discussionsupporting
confidence: 72%
“…In an Xenopus oocyte assay with the injection of antisense oligonucleotides, G ␣q was identified as a mediator of the BB 1 receptor response (Shapira et al, 1994). With an in situ reconstitution assay with purified G protein ␣ subunits, it was found that cells expressing the BB 1 receptor activated G ␣q , but not G ␣t or G ␣i/o .…”
Section: G Bb 1 Receptor Signaling Activation and Modulatorymentioning
confidence: 99%
“…The initial inward deflection prior to IP 3 or Ca 2ϩ injection is a mechanical artifact due to insertion of the injection pipette. for other pertussis toxin-insensitive G proteins, including G␣ q and G␣ 11 , have been cloned from Xenopus (37,40). Using antibodies against the C-terminal sequence of mouse G q it has been shown that oocytes express several forms of the G q family of ␣ subunits (22).…”
Section: G␣ 16 Inhibition Of Ligand-induced CLmentioning
confidence: 99%